How clinical supervision is accomplished in groups of pre-registration student nurses when they are facilitated by nurse educators - Sheppard, Fiona (2018)
The literature suggests many positive benefits of Group Clinical Supervision (GCS) with pre-registration students facilitated by lecturer supervisors. It helps students hone their reflective and critical decision-making skills, and engagement demonstrates working with peers is strongly linked with developing self-awareness and empathic understanding of others. It normalises shared practice experiences and is experienced as supportive and restorative. However, positive findings of GCS are enhanced when the learning environment feels safe and sensitively facilitated and reduced when this is diminished. In addition, several issues are identified as problematic, intriguing or unexplored. These include; methodological approaches, group and supervisory relationships, perceived coercion versus engagement, perceived value of challenge, lack of clarity around the operationalisation of functional and reflective models, differing experiences of men and women.